Neuroma Management: Capping Nerve Injuries With an Acellular Nerve Allograft Can Limit Axon Regeneration. (March 2021) - Hong, Thomas; Wood, Ian; Hunter, Daniel A.; Yan, Ying; Mackinnon, Susan E.; Wood, Matthew D.; Moore, Amy M.
Background: Management of painful neuromas continues to challenge clinicians. Controlling axon growth to prevent neuroma has gained considerable traction. A logical extension of this idea is to therefore develop an approach to control and arrest axon growth. Given the limits in axonal regeneration across acellular nerve allografts (ANAs), these constructs could provide a means to reliably terminate axon regeneration from an injured nerve. The purpose of this study was to determine if attaching an ANA to an injured nerve could provide a means to control and limit axon regeneration in a predictable manner.Methods: Twenty (20) adult rats received a sciatic nerve transection, where only the proximal nerve was repaired using an ANA of variable length (0.5, 2.5, and 5.0 cm) or left unrepaired (control). The nerves were harvested 5 weeks post-operatively for gross and histomorphometric analysis. The extent of myelinated axons in regenerated tissue was quantified.Results: At 5 weeks, limited axon regeneration within the ANAs was observed. All lengths of ANAs lead to reduced myelinated axon numbers in the most terminal tissue region compared to untreated injured nerve ( P = .002). Additionally, ANA length 2.5 cm or greater did not contain any axons at the most terminal tissue region.Conclusions: This study demonstrates a proof of concept that ANAs attached to the proximal end of an injured nerve can limit axon growth in a controlled manner. Furthermore, the extent of axon growth from the injured nerve into the ANA is dependent on the ANA length.